Roentgen stereophotogrammetric analysis for assessing migration of total hip replacement femoral components. - Kiss, J; Murray, D; Turner-Smith, A; Bulstrode, C (1995)
A new Roentgen stereophotogrammetric analysis system, using a biplane technique, has been developed to determine the migration and rotation of total hip replacement (THR) femoral components in three dimensions. Stainless steel marker balls were injected into the femur during the operation. The patients stood within a calibration frame during the X-ray. The two exposures were taken consecutively allowing radio-opaque shutters to be moved in front of the films to prevent fogging. Studies with a model demonstrated that the system was capable of measuring the position of an implant to better than 0.11 mm (2 SD). In vivo measurements demonstrated that the migration rate of the different parts of the femoral component could be determined with an accuracy of 0.25 to 0.50 mm/year. By considering the accuracy determined in different ways, methods for improving the system have been identified. The migration and rotation rate of 58 Hinek cemented femoral components was studied for four years. Migration was three to five times greater (p < 0.001) during the first year than subsequently. The prosthesis head moved the most during the first year (0.94 mm). A better understanding of the cause of implant failure could be obtained by studying the early migration of different types of prosthesis and comparing this with their clinical results and design features.